(3GdQbI aj CNjGQ GdUGdMjf hCNHGQges - (3YHO Gddg Hf CMeO Hf eMeO Hf bOGeI GdLeGYjdj GdebOSj Ke GdOeTbj GdMfHdj, ehab GdOjf GHf bOGeI , J (B620 (3gs ((3eMeO Hf ESeGYjd GdHbdj GdMfHdj s)
(3ChdgG (B:s
(3CeG HYO , aEfj CMHHJ Cf CLeY CNHGQ COGhj HgG bShI bdHj ade CQ CLdH dg hdG CLeY deG CQOJ ef CNHGQ GdUGdMjf s
(3BNQgG (B:s
(3gPG MOjK ZQjH dG CYde (B[(3ef(B] (3MOK Hg EdG GHfg YHO Gddg Hf hgH ef gPg GdQhGjI s
(3YdjgG Jedc HGSe eUWai Hf EHQGgje CZG TjNHfOQRGOIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B30 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B459s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B398 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B689 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B206 s
Keywords: (3GdJGQjNs